Sexualidade indígena na internet : os discursos interétnicos sobre a iniciação sexual dos Chiquitanos em Mato Grosso - Santos, Renata Cristina dos (2019)
This dissertation sought to analyze the Chiquitana female sexual initiation linked to a media discourse of suspected sexual abuse involving Chiquitanos from Mato Grosso. To this end, the focus is on a period of intense propagation of the problem that is related to the way that these facts are put by the media to expose the lives of these indigenous people with prejudice. News from “digital newspapers” and internet publications on the most varied topics were analyzed, with a specific cut on the cases of suspected sexual abuse of Chiquitan men against Chiquitan minors. The objective, then, is to provoke a reflection on Chiquitana female sexual initiation in an interethnic context through contents and speeches reproduced in online newspapers, in digital publications and in public domain speeches and to map the conflicts between the occurrence of these facts and the imposition of the State. The proposed hypotheses are related to issues such as land demarcation and identity affirmation, in addition to the discussion about the need to review conduct on practices considered outside the broader cultural custom. In this way, the results are found, in part, in the hypotheses, and raise other types of more in-depth discussions about prejudice, violence, and oppressive mechanisms of non- indigenous society over indigenous people.